ChemInform Abstract: Palladium(II)‐Catalyzed Enantioselective C(sp3)—H Activation Using a Chiral Hydroxamic Acid Ligand. Issue 1 (January 2015) - Xiao, Kai‐Jiong; Lin, David W.; Miura, Motofumi; Zhu, Ru‐Yi; Gong, Wei; Wasa, Masayuki; Yu, Jin‐Quan
Abstract The absolute configurations of compounds (III) and (V) are tentatively assigned in analogy to that of (Vc) which is determined by X‐ray crystallographic analysis.